2021
DOI: 10.1002/eji.202048878
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A expressed on neutrophil extracellular traps promotes mesenchymal stem cell differentiation toward bone‐forming cells in ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is an inflammatory disease characterized by excessive bone formation. We investigated the presence of neutrophil extracellular traps (NETs) in AS and how they are involved in the osteogenic capacity of bone marrow mesenchymal stem cells (MSCs) through interleukin‐17A (IL‐17A). Peripheral neutrophils and sera were obtained from patients with active AS and healthy controls. NET formation and neutrophil/NET‐associated proteins were studied using immunofluorescence, immunoblotting, qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 70 publications
1
30
0
1
Order By: Relevance
“…We have recently demonstrated the involvement of NETs and NET-associated cytokines in UVB-induced skin inflammation [9], and others also demonstrated association of IL-17 with neutrophil NETs [76] or extracellular traps released by TH17 cells [57]. In the current study, we found PAF-induced expression of IL-17A, TNFα, IFNγ, and IFNα in neutrophils, and these cytokines can be released to the extracellular space with NETs during NETosis.…”
Section: Discussionsupporting
confidence: 71%
“…We have recently demonstrated the involvement of NETs and NET-associated cytokines in UVB-induced skin inflammation [9], and others also demonstrated association of IL-17 with neutrophil NETs [76] or extracellular traps released by TH17 cells [57]. In the current study, we found PAF-induced expression of IL-17A, TNFα, IFNγ, and IFNα in neutrophils, and these cytokines can be released to the extracellular space with NETs during NETosis.…”
Section: Discussionsupporting
confidence: 71%
“…We have recently demonstrated the involvement of NETs and NET-associated cytokines in UVB-induced skin inflammation 9 , and others also demonstrated the association of IL-17 with neutrophil NETs 77 or extracellular traps released by TH17 cells 58 . In the current study, we found PAF-induced expression of IL-17A, TNFα, IFNγ, and IFNα in neutrophils, and these cytokines can be released with NETs to the extracellular space during NETosis.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we found for the rst time that IL-17A has a role in enhancing osteogenic differentiation of LFCs. Numerous evidence has previously shown that IL-17A can promote bone formation [19,[36][37][38]]. However, some other studies have concluded the opposite [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of experimental evidence indicate that IL-17A plays an signi cant role in promoting heterotopic ossi cation [18]. In addition, IL-17 could promote osteogenic differentiation of human mesenchymal stem cells [19]. However, its effect on osteogenic differentiation of ligamentum avum cells (LFCs) remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%